Exome and genome sequencing in adults with undiagnosed disease: a prospective cohort study. Issue 4 (24th June 2020) - Shickh, Salma; Gutierrez Salazar, Mariana; Zakoor, Kathleen-Rose; Lázaro, Conxi; Gu, Jessica; Goltz, Jamie; Kleinman, Dakota; Noor, Abdul; Khalouei, Sam; Mighton, Chloe; Reble, Emma; Kodida, Rita; et al.
Abstract : Background: Exome and genome sequencing have been demonstrated to increase diagnostic yield in paediatric populations, improving treatment options and providing risk information for relatives. There are limited studies examining the clinical utility of these tests in adults, who currently have limited access to this technology. Methods: Patients from adult and cancer genetics clinics across Toronto, Ontario, Canada were recruited into a prospective cohort study evaluating the diagnostic utility of exome and genome sequencing in adults. Eligible patients were ≥18 years of age and suspected of having a hereditary disorder but had received previous uninformative genetic test results. In total, we examined the diagnostic utility of exome and genome sequencing in 47 probands and 34 of their relatives who consented to participate and underwent exome or genome sequencing. Results: Overall, 17% (8/47) of probands had a pathogenic or likely pathogenic variant identified in a gene associated with their primary indication for testing. The diagnostic yield for patients with a cancer history was similar to the yield for patients with a non-cancer history (4/18 (22%) vs 4/29 (14%)). An additional 24 probands (51%) had an inconclusive result. Secondary findings were identified in 10 patients (21%); three had medically actionable results. Conclusions: This study lends evidence to the diagnostic utility of exome or genome sequencing in an undiagnosed adult population. The significant increase in diagnostic yield warrants the use of this technology. The identification and communication of secondary findings may provide added value when using this testing modality as a first-line test.